2022
DOI: 10.1016/j.radonc.2021.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Online adaptive radiotherapy potentially reduces toxicity for high-risk prostate cancer treatment

Abstract: Background and purpose: With daily, MR-guided online adapted radiotherapy (MRgART) it may be possible to reduce the PTV in pelvic RT. This study investigated the potential reduction in normal tissue complication probability (NTCP) of MRgART compared to standard radiotherapy for high-risk prostate cancer. Materials and methods: Twenty patients treated with 78 Gy to the prostate and 56 Gy to elective pelvic lymph nodes were included. VMAT plans were generated with standard clinical PTV margins. Additionally to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 43 publications
(61 reference statements)
1
20
1
Order By: Relevance
“…Despite the lack of previous MRgSBRT studies for direct comparisons of clinical outcome, our preliminary clinical outcome seemed to be well aligned with the simulation results by Christiansen et al [ 47 ], although slightly larger PTV margins were applied in our study. Long-term clinical outcome of our study will be presented with further follow-up.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Despite the lack of previous MRgSBRT studies for direct comparisons of clinical outcome, our preliminary clinical outcome seemed to be well aligned with the simulation results by Christiansen et al [ 47 ], although slightly larger PTV margins were applied in our study. Long-term clinical outcome of our study will be presented with further follow-up.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, a simulation study by Christiansen et al [ 47 ] showed that online adaptive MRgRT might reduce the dose to the surrounding tissues compared to standard RT for HR-PC patients by allowing tighter PTV margins to both the prostate (3 mm, 4 mm, and 5 mm in R-L, S-I, and A-P) and pelvic lymph node (uniform 2 mm) CTVs. Such observed reductions in doses to OARs could translate to reduced risks of acute GI toxicity and late bladder toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given a considerably long treatment time in MRgSBRT, it is reasonable to conclude that a posterior margin of 3 mm and an SI margin of 5 mm might need to be slightly increased to achieve adequate PTV coverage in the absence of intrafractional motion monitoring. Compared with previously published data for gantry-based SBRT 15 and MRgRT on MR-Linac, 29 the present data show a smaller AP margin, but a larger SI margin, thus a more pronounced margin in the SI direction. This could be due to the endorectal balloon used in our protocol for MRgSBRT, as the rectum wall distension might be suppressed by the inserted rectal balloon, resulting in consistent rectum shape through the treatment course.…”
Section: Discussioncontrasting
confidence: 50%
“…Radiation therapy is one of the primary treatments for cancer. Recently, various radiation therapy techniques such as image-guided radiotherapy and adaptive radiotherapy have been adopted by clinics to deliver highly conformal doses to tumors while sparing normal tissues [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%